Spinocerebellar ataxia type 10: common haplotype and disease progression rate in Peru and Brazil. (31st May 2017) - Gheno, T. C.; Furtado, G. V.; Saute, J. A. M.; Donis, K. C.; Fontanari, A. M. V.; Emmel, V. E.; Pedroso, J. L.; Barsottini, O.; Godeiro‐Junior, C.; van der Linden, H.; Ternes Pereira, E.; Cintra, V. P.; et al.
Abstract : Background and purpose: Spinocerebellar ataxia type 10 is a neurodegenerative disorder that is due to an expanded ATTCT repeat tract in the ATXN10 gene. Our aim was to describe clinical characteristics and intragenic haplotypes of patients with spinocerebellar ataxia type 10 from Brazil and Peru. Methods: Expanded alleles were detected by repeat‐primed polymerase chain reaction. Disease progression was measured by the Scale for the Assessment and Rating of Ataxia, and the Neurological Examination Score for Spinocerebellar Ataxias when possible. Haplotypes were constructed based on polymorphic markers within and outside the gene. Results: Thirteen new families were diagnosed (three from Peru). Patients from three Brazilian families diagnosed previously were also reassessed. In total, 25 individuals (16 families) were evaluated. Mean (± SD) age at onset and disease duration were 34.8 ± 10.2 and 12 ± 8 years, respectively. Common findings were ataxia, dysarthria/dysphagia, nystagmus, pyramidal signs, ophthalmoparesis and seizures. No associations were found between clinical findings and geographical origins. Twelve patients living in remote regions were examined only once. In the remaining individuals, the Scale for the Assessment and Rating of Ataxia score, and Neurological Examination Score for Spinocerebellar Ataxias worsened by 0.444 (95% CI, −0.088 to 0.800) and 0.287 (95% CI, −0.061 to 0.635) points/year, respectively. A common haplotype, 19CGGC14, was found in 11/13 of Brazilian and in 1/3 of Peruvian families. Conclusions: The progression rate was slower than in other spinocerebellar ataxias. A consistently recurrent intragenic haplotype was found, suggesting a common ancestry for most, if not all, patients.